(untitled) (The Pakistan Development Review, 2009)
This paper establishes empirically the causal relationship and long run relationship between government expenditures and government revenues for the case of Pakistan from 1972 to 2007. Fiscal policy, a short run issue, but that can have testing macro economic consequences. Fiscal policy is viewed as an instrument to mitigate short run fluctuations. In this paper we examine tax/spend or spend/tax hypothesis. For this purpose, bi-directional Granger causality will be applied for instance flow from government expenditure to revenue or revenue to government expenditure. This issue has been concerned with intretemporal relationship between revenue and expenditure, so to check long run relationship Engel Granger cointegration will be used. For checking data stationary, non stationary unit root, and ADF/DF approaches give the proof for this hypothesis. The results show the presence of co-integration between government expenditure and tax revenue variables implying evidence of a stable long-run relationship between them. The Granger Causality test suggest the unidirectional causality flow from government expenditure to tax revenue. Keywords: Government Expenditures, Government Revenues, Granger Causality, Stationary, Co-integration